Three Warriors from Laweyan: Tiga Pendekar Dari Laweyan - Purwanta, Hieronymus; Victor Novianto (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This study attempts to examine the important role of three Laweyan warriors in the development of the Pajang Duchy under the Hadiwijaya government. The research uses historical methods. The collection of sources was mainly carried out using traditional historiography, namely Babad. The analysis used a hermeneutic and political culture approach. Hermeneutics was used primarily to find the message contained in the narrative of the Babad as a literary worship. On the other hand, political culture was carried out to analyze the behavior of historical figures from the perspective of Javanese knightly ethics. The results show that politically, the three warriors from Laweyan, namely Ki Ageng Penjawi, Ki Ageng Pemanahan, and Ki Juru Mertani, found it easy to have a career in the Pajang Duchy because of the good relationship between Ki Ageng Henis and Hadiwijaya. However, it did not make them self-indulgent. The three Laweyan warriors showed their abilities, so they were worthy of being trusted to become military leaders of the Pajang Duchy. The milestones they achieved were defeating Arya Penangsang and making the Pajang Duchy a Sultanate. The achievement developed their careers into Dukes with territories in Pati and Mataram.